AN ANALYSIS OF METAPHORIC TRANSLATION OF THE FAULT IN OUR STARS NOVEL - Maya Nurfadilah (Universitas Muhammadiyah Tangerang, 2019)
This research aimed at identifying metaphor translation strategy used in The Fault in Our Stars novel based on theory of Bassnett, Lefevere, 1993; Snell-Hornby, 2006 and the accuracy between the source language (SL) in English and target language (TL) in Bahasa Indonesia. The object of this research is The Fault in Our Stars novel by John Green published in 2012 originally in English and the translated novel by Ingrid Dwijani Nimpoeno in Bahasa Indonesia under Qanita Publisher copyright. The researcher focused on metaphoric expressions in the novel and analyzed the strategy used based on Bassnet, Lefevere and Snell-Hornby‟s theory. The researcher also assessed the accuracy of the translation results in range accurate, less accurate and inaccurate based on Accurate Translation Rate proposed by Nababan, Nuraeni and Sumardiono (2012). In the end, the researcher found that most of the strategy used by translator is metaphor into same metaphor (69%), second is metaphor into different metaphor (20%), and the last is metaphor into sense (11%). The accuracy of the translation is rated by two lecturers of English Education Study Program of Teachers Training and Education Faculty of Muhammadiyah University of Tangerang with the results 79% translations are accurate, 21% translations are less accurate and 0% translations are inaccurate.